Spectral broadening of 112 mJ, 1.3 ps pulses at 5 kHz in a LG10 multipass cell with compressibility to 37 fs - Kaumanns, Martin; Kormin, Dmitrii; Nubbemeyer, Thomas; Pervak, Vladimir; Karsch, Stefan (Optics letters, 2021)
The first-order helical Laguerre-Gaussian mode (also called donut mode) is used to improve the energy throughput of nonlinear spectral broadening in gas-filled multipass cells. The method proposed in this Letter enables, for the first time to the best of our knowledge, the nonlinear spectral broadening of pulses with energies beyond 100 mJ and is suitable for an average power of more than 500 W while conserving an excellent spatio-spectral homogeneity of ∼98% and a Gaussian-like focus profile. Additionally compressibility from 1.3 ps to 37 fs is demonstrated.The first-order helical Laguerre-Gaussian mode (also called donut mode) is used to improve the energy throughput of nonlinear spectral broadening in gas-filled multipass cells. The method proposed in this Letter enables, for the first time to the best of our knowledge, the nonlinear spectral broadening of pulses with energies beyond 100 mJ and is suitable for an average power of more than 500 W while conserving an excellent spatio-spectral homogeneity of ∼98% and a Gaussian-like focus profile. Additionally compressibility from 1.3 ps to 37 fs is demonstrated.